Wizualizacja danych nominalnych oraz różnego typu danych porządkowych w procedurze skalowania optymalnego - Rószkiewicz, Małgorzata (Visualization of Categorical Data in Procedure of Optimal Scaling, 2009)
The paper focuses on the topic of optimal scaling of categorical data - the method of building the quantitative representation of qualitative experiences. The main goal of non-metric data visualization is to extract as much information as possible from linear and nonlinear relations among variables. Optimal scaling is a method to accomplish this goal by assigning optimal spaced weights to variables. The paper presents some examples of transformation categorical data (nominal and ordinal) to the procedure of optimal scaling.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 86, s. 11-19